Distributional Patterns of Herb Growth forms along Elevation and Grazing Pressure Gradient - Singh, Sanjay (Indian Forester, 2004)
Distribution of herb growth forms in the understory of some village resource forests in Central Himalaya has been studied along elevation (800-1 ,610m) and grazing pressure (least to severe) gradient. Erect and umbrella-like forms registered an increase in their share in the herb growth form spectrum with increase in elevation while basal leaf forms and sprawling mats exhibit better representation at low elevation. Grazing most adversely affects erect forms but promotes herb growth form diversity. Umbrella-like forms , basal leaf forms and sprawling mats prefer disturbed sites. Overall , better growth form diversity occurred at low elevation and grazed sites.